Intervention in the Collective Adoption of Agreements in a Society and Criminal Liability - Meini Méndez, Iván (2004)
In the business environment, particularly in a company, collective agreements determine the stability and continuity of the company. The approval of such agreements must therefore be carried out in accordance with national company law. However, as the author points out, unlawful collective decisions can have criminal consequences. In this sense, the aim of this article is to determine who may be criminally liable on the basis of the role played by the person in preparing or signing the agreement; what is the scope of unlawful executive agreements and agreements that require subsequent execution; and how the principle of reliance and mistake of type should be assessed in these cases.